An Exploratory Review of Kushthaghna Mahakashaya in Skin Disorders w.s.r. to Visha - Patel, Narsingh; Sharma, Anita; Kadu, Amol Sudhakar (International Research Journal of Ayurveda & Yoga, 2022)
Background: The Ayurveda treatises are collection of vast knowledge regarding medical and environmental aspects. It has a separate branch called Agada Tantra which deals with the toxicological aspects. We aim to evaluate this knowledge regarding dermatological manifestation due to Visha (toxins) vis-à-vis contemporary knowledge. Objective: The objective of this study is to analyze the rationality and applicability of Kushthaghna Mahakashaya in the prevention and management of skin disorders caused by various type of poisons. Data Source: The references available in classical texts, various Nighantu and research articles regarding the various forms of poisons and their dermatological manifestations were analyzed and compared to the knowledge available in contemporary medical literatures. Review methods: A sincere study of classical Ayurveda text-books and their available commentaries along with modern texts, websites and articles has been done to explore the importance of Kushthaghna Mahakashaya in various skin diseases. Result and conclusion: The herbs mentioned in the Kushthaghna Mahakashaya were scientifically evaluated in various preclinical and clinical studies and showed antiviral, immune-modulatory, anti-inflammatory, anti oxidant, anti-cancerous, cardio-protective, neuroprotective, anti- fungal, and anti- bacterial activity, according to the results of the literature quest. The proper application of Kushthaghna Mahakashaya plants will aid in the prevention and treatment of skin diseases.